EXPLORING THE KEY CHALLENGES IN IMPLEMENTING SUSTAINABLE WASTE MANAGEMENT PRACTICES - Danish Khan; Abid Ghafoor Chaudhry (International Journal of Contemporary Issues in Social Sciences, 2024)
This research topic focus on exploring anthropological insights with references to key challenges in implementing sustainable waste management practices. In developing nations, policies are implemented to lessen the negative effects of a large amount of waste produced by rapid urbanization and accelerated industrialization. Nonetheless, with regards to the administration of metropolitan strong waste (MSW), which requires the joint effort of various partners and a complete technique for accomplishing maintainability objectives and strategies for urban communities, these approaches are a long way from laying out systems that address the issues of society. With its hypothetical, down to earth, and political ramifications, this study empowers the accomplishment of practical improvement objectives, gives natural, financial, and cultural commitments, and fills in as an upgrade for the advancement of multidisciplinary public strategies. In the world's major cities, the issue of urban solid waste management (SWM) is a major one that is getting worse with rapid urbanization.